JUSTIFICATION OF THE USE OF THE METHOD OF LYMPHATIC THERAPY TO IMPROVE THE RESULTS IN THE COMPLEX TREATMENT OF ULCERATIVE COLITIS - Ruziev Axtam Ergashovich (Research Parks Publishing LLC, 2020)
Ulcerative colitis is one of the most significant problems of modern gastroenterology. The constant increase in morbidity, disability of the population, as well as the high prevalence of the overwhelming number of cases among the working-age population aged 20-40 years, makes this pathology socially significant [7; 8; 9].